Update on enteroviral protease 2A: Structure, function, and host factor interaction - Ying Liu; Jichen Li; Yong Zhang (Elsevier, 2023)
Enteroviruses (EVs) are human pathogens commonly observed in children aged 0-5 years and adults. EV infections usually cause the common cold and hand-foot-and-mouth disease; however, more severe infections can result in multiorgan complications, such as polio, aseptic meningitis, and myocarditis. The molecular mechanisms by which enteroviruses cause these diseases are still poorly understood, but accumulating evidence points to two enterovirus proteases, 2Apro and 3Cpro, as the key players in pathogenesis. The 2Apro performs post-translational proteolytic processing of viral polyproteins and cleaves several host factors to evade antiviral immune responses and promote viral replication. It was also discovered that coxsackievirus-induced cardiomyopathy was caused by 2Apro-mediated cleavage of dystrophin in cardiomyocytes, indicating that cellular protein proteolysis may play a key role in enterovirus-associated diseases. Therefore, studies of 2Apro could reveal additional substrates that may be associated with specific diseases. Here, we discuss the genetic and structural properties of 2Apro and review how the protease antagonizes innate immune responses to promote viral replication, as well as novel substrates and mechanisms for 2Apro. We also summarize the current approaches for identifying the substrates of 2Apro to discover novel mechanisms relating to certain diseases.